Platelet Activity In Vivo in Hyperlipoproteinemia – Importance of Combined Hyperlipidemia - Bröijersén, Anders; Hamsten, Anders; Eriksson, Mats; Angelin, Bo; Hjemdahl, Paul (Thrombosis and Haemostasis, 1998)
Platelet hyperactivity in vitro is found in patients with isolated hypercholesterolemia. It is, however, less well established if platelet activity in vivo is enhanced, and if there are differences between various types of hyperlipoproteinemia.Platelet function in vivo was studied at rest and during mental stress in men with isolated hypercholesterolemia (phenotype IIa; n = 21) or combined hyperlipidemia (phenotype IIb; n = 29), and age-matched normolipidemic controls (n = 41). The urinary excretion of 11-dehydrothromboxane B2 was elevated in patients compared to controls (IIa, p <0.05; IIb, p <0.001), and higher in type IIb than in IIa patients (p <0.05). Platelet secretion, assessed as plasma β-thromboglobulin levels, was higher in type IIb patients compared to controls (p <0.01) and type IIa patients (p <0.05) during mental stress. The urinary excretion of β-thromboglobulin was also elevated in type IIb patients compared to controls (p <0.05). Platelet aggregability at rest, as measured by filtragometry ex vivo was, however, reduced in both patient groups compared to controls (p <0.05). No correlations were found between plasma lipoprotein levels and markers of platelet function in vivo. Type IIb patients had higher plasma fibrinogen levels and higher leukocyte counts than controls (p <0.05 and p <0.001) and type IIa patients (p <0.05 and p = 0.06). Thromboxane excretion was positively related to fibrinogen levels and leukocyte counts (p <0.01 for both). Preliminary data regarding serum TNF-α also indicated an elevation of this inflammatory cytokine in type IIb patients (p <0.05 vs controls).In conclusion, thromboxane generation and platelet secretion in vivo are enhanced in patients with hypercholesterolemia, and particularly so among patients with concomitant elevation of plasma triglycerides. The mechanism is unknown, but inflammatory mediators may be involved. The present findings are of interest in relation to the role of triglycerides in coronary artery disease.